(3TQM OjhGf GHf MUjfI GdSdeis - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s; (3CHhGdaJM GdMSf Hf YHO Gddg Hf CMeO Hf YHO GdLHGQ GdSdej,J (B457 (3g` s ((3GdNdjd Hf Ndjag GdYRjR Gdeci GdQhei GdMfai s)
(3ChdgG (B:s
(3GdOgQ eOjQ Whjd jLhR Cf jMOK ai CNQg ceG jMOK ai Chdg , dCf Gddg SHMGfg bOjQ Ydi GdeeJfYGJ s
(3BNQgG (B:s
(3jbhdhG agh eSYO aGbJUQhG Ydi bhdge (B: (3agh eSYhO , hcCfge Hfhg Ydi SYO hMci bhe SYOg Gddg hCSYOg GfJgi TQM OjhGf GHf CHj MUjfI HMeO Gddg s
(3CHh MUjfI GdSdei gh GdCejQ CHf GdaJM GdMSf GHf YHO Gddg Hf CMeO Hf YHO GdLHGQ GdeJhai (B457s
(3hHBNQgG JQLeg dUGMH GdOjhGf de JSJced hCNQi dTGQMg CHj GdYdGA GdeYQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs